Assessing Thailand’s financial vulnerability : An early warning approach - Chin, Hong Puah; Tai, Hock Kuek; M. Affendy, Arip (Prague Development Center,Prague Development Center s.r.o., 2017)
This paper intends to assess financial vulnerability in Thailand through the construction of a financial vulnerability indicator (FVI). This early warning system has been developed using the signals approach proposed by Kaminsky and Reinhart (1999), followed by composite indicator construction. The period under study spans from January 2000 through to December 2016. Our empirical findings indicate that exports has the lowest noise-to-signal ratio (0.13), followed by real GDP (0.15) and house price index (0.20). These suggest that financial crises are usually preceded by a weakening in exports, a slowdown in the economy and a decline in house price. For Thailand, four major financial episodes are successfully outlined during the study period, demonstrating the effectiveness of an early warning system in financial vulnerability forecasting.